Knockout of IL-6 mitigates cold water-immersion restraint stress-induced intestinal epithelial injury and apoptosis - Zhang, Yuan; Duan, Chujun; Wu, Shuwen; Ma, Jingchang; Liu, Yongming; Li, Wenpeng; Wang, Tingting; Yang, Lu; Cheng, Kun; Zhuang, Ran (Frontiers in immunology, 2022)
Interleukin-6 (IL-6) is essential for maintaining intestinal epithelial homeostasis. Although cold water-immersion restraint (CWIR) stress is commonly used to induce in vivo gastric injury, it also affects intestinal epithelial permeability. Although IL-6 is increased in response to acute physiological and psychological stress, its exact effects on the pathophysiology of the intestinal epithelium in response to acute CWIR stress remain unknown. We used IL-6 knockout (KO) mice with acute CWIR modeling to investigate the effect of IL-6 deficiency on intestinal epithelial morphology and pathological damage using histological staining assays under the acute stress. We detected jejunal epithelial apoptosis using TUNEL and standard molecular experiments. CWIR caused intestinal epithelial damage, which was alleviated by the absence of IL-6, as evidenced by morphological changes and goblet cell and intestinal permeability alteration. IL-6 KO also reduced CWIR-mediated inflammatory levels and improved stress defense. Meanwhile, IL-6 deficiency decreased the intestinal epithelial apoptosis induced by CWIR administration. This IL-6 KO-led effect depended more on mitochondrial AIF signaling rather than the traditional caspase pathway. As a result, we concluded that acute CWIR-induced severe intestinal damage and jejunal epithelium apoptosis could be alleviated by IL-6 deficiency, implying a protective effect of IL-6 deficiency on the intestines under acute stress. The findings shed new light on treating CWIR-induced intestinal disorders by inhibiting IL-6 signaling.